ATP activates regulatory T cells in vivo during contact hypersensitivity reactions - Ring, Sabine; Enk, Alexander; Mahnke, Karsten (The journal of immunology, 2010)
CD4+CD25+Foxp3+ regulatory T cells (Tregs) require activation to develop their full suppressive capacity. Similar to conventional T cells, Tregs can be activated via their TCRs; however, other means may be in place. We injected naive and nonactivated Tregs, being CD69−CD44lowCD62L+ into mice, and analyzed their phenotype after sensitization or challenge with the contact sensitizer 2,4,6-trinitro-1-chlorobenzene. We found that Tregs acquired an activated phenotype (CD69+CD44highCD62L−) in the draining lymph node after sensitization. In contrast, Ag challenge activated Tregs in the blood. This tissue-specific activation was induced by ATP, which was released at the respective tissue sites after sensitization or challenge, respectively. To demonstrate that activation was also essential for the induction of the suppressive function of Tregs, Tregs were treated with ATP receptor antagonists. In this study, we show that ATP receptor antagonists abrogated the suppressive effects of injected naive Tregs in contact hypersensitivity reactions. Thus, these data indicate that activation of Tregs via ATP in vivo provides a novel pathway of stimulating the suppressive function of Tregs.
Gesehen am 24.05.2023